Pengaruh Komposisi Media Tanam Terhadap Pertumbuhan Tanaman Kangkung Darat (Ipomea Reptans Poir) - Harlina Kusumatuti (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2023)
Morning glory plant (Ipomea reptans Poir) is a type of vegetable that has various benefits for human growth and health, such as containing vitamins A, B, C, protein, calcium, phosphorus, carotene, as well as mineral ingredients, and iron, therefore many enthusiasts of morning glory plants. Morning glory cultivators often use synthetic chemicals excessively, causing unfavorable soil conditions and causing low morning glory production. Efforts that can be made to improve soil quality for morning glory cultivation are by reducing the use of chemicals and cultivating morning glory plants organically. This research was conducted to determine the type of planting medium and composition of the best growing medium for the growth of morning glory plants. The treatment applied soil:compost (1:1) and (0:1) while the control (1:0) using Complete Randomized Block Design with 5 replications. The results of the study showed that the treatment of growing médium with compost showed a positive effect on the growth of morning glory plants including plant height, number of leaves, leaf length, and root length.